Instructional Effectiveness of a Computer-Supported Program for Teaching Reading Comprehension Strategies - Lopez-Villarroel, M; Ponce-Arias, H (2012)
This article examines the effectiveness of a computer-based instructional program (e-PELS) aimed at direct instruction in a collection of reading comprehension strategies. In e-PELS, students learn to highlight and outline expository passages based on various types of text structures (such as comparison or cause-and-effect) as well as to paraphrase, self-question, and summarize. The study involved 1041 fourth-grade elementary students from 21 schools distributed in three regions in central Chile. Participant teachers integrated this program into the Spanish language curriculum, instructing their students during thirty sessions of 90 min each during one school semester. Pretest-to-posttest gains in reading comprehension scores were significantly greater for students instructed with this program than for students who received traditional instruction (d = .5), with particularly strong effects for lower-achieving students (d = .7). The findings support the efficacy of direct instruction in specific learning strategies in a computer-based environment. © 2012 Elsevier Ltd. All rights reserved.